Дослідження активування природного клиноптилоліту надвисокочастотними електромагнітними випромінюваннями - Грабаровська, А. С.; Знак, З. О.; Оленич, Р. Р.; Hrabarovska, A. S.; Znak, Z. O.; Olenych, R. R. (Lviv Politechnic Publishing House, 2018)
Досліджено вплив потужності надвисокочастотного електромагнітного випроміню- вання на ступінь дегідратації природного сорбенту – клиноптилоліту. Встановлено, що існує певне порогове значення потужності випромінювання, за якого відбувається дегідратація клиноптилоліту. Встановлено, що активований в електромагнітному полі клиноптилоліт володіє вищою, ніж неактивований, сорбційної здатністю щодо сполук різної природи, зокрема сульфуру(IV) оксиду та формальдегіду.

The influence of the power of ultrahigh-frequency electromagnetic radiation on the degree of dehydration of a natural sorbent – clinoptilolite was investigated. It is established that there is a certain threshold value of radiation power, in which dehydration of clinoptilolite occurs. It was established that clinoptilolite activated in the electromagnetic field has a higher than unactivated sorption ability for compounds of different nature, in particular, sulfur(IV) oxide and formaldehyde.
Investigation of activation of natural clinoptylolite by high-frequency electromagnetic radiation
Keywords: клиноптилоліт; активація; електромагнітні випромінювання; дегідратація; clinoptilolite; activation; electromagnetic radiation; dehydration